Development IoT-based Infant Monitoring System for Preventing Sudden Infant Death Syndrome (SIDS) with Abnormal Condition Notifications and Lost Data Analysis - Ananta, Erick Dwi; Syaifuddin, Syaifuddin; Soetjiatie, Liliek; Utomo, Bedjo (Jurnal Teknokes, 2023)
Sudden infant death syndrome or SIDS is the sudden death of a healthy baby under 1 year of age that occurs without any symptoms. It can be triggered by various factors, ranging from the baby's sleeping position to the baby's physical condition that has not reached a certain stage of development. Checking the baby's body temperature and heart rate is a very important element to monitor the baby's condition. In addition, checking body temperature and heart rate can also prevent febrile seizures that can cause epilepsy. Therefore, a tool is needed that can monitor the body temperature and heart rate of babies in real time and with an efficient mechanism. The purpose of this research is to conduct real-time monitoring with vital parameters of Respiration Rate using Piezo Electric sensor and heart rate monitoring using MAX30100 sensor. This research method is the design of a respiration and heart rate monitoring tool using piezoelectric sensors and ESP 32. The measurement results show that the largest difference value with the comparison tool is 28.74% and the smallest is 0.00%. suggestions and recommendations in this study on the right sensor placement so that effective results are obtained and the output results can be accessed via the website by doctors and other health workers and the existence of telegram notifications if conditions are abnormal so as to prevent SIDS..